Design and Development of a Marine Data Acquisition System for Inertial Measurement in Wind Powered Yachts - Bergeron, Alexandre (Université d'Ottawa / University of Ottawa, 2012)
This thesis presents the design of an inertial measurement data acquisition system intended for use in sailboats. The variables of interest are 3-axis acceleration, 3-axis rotation, GPS position/velocity, magnetic compass bearing and wind speed/direction. The design focus is on low-cost micro-electromechanical systems (MEMS) based technology and demonstrating the validity of these technologies in a scientific application. A prototype is constructed and submitted to a series of tests to demonstrate functionality and soundness of the design. These tests range from bench tests to full scale application. Contributions of this thesis include the novel application of inertial measurement unit (IMU) technology to a sailboat racing application, the integration of all instrumentation, creative ruggedised packaging and emphasising the use of low-cost commercial off-the-shelf (COTS) technology.
Keywords: Sailboat; Yacht; Wind; Data Acquisition; Marine; IMU; MEMS; Inertial; Measurement; Design; Development; GPS